Evidence for long‐term change in length, mass and migration phenology of anadromous spawners in French Atlantic salmon Salmo salar. Issue 6 (4th May 2017) - Bal, G.; Montorio, L.; Rivot, E.; Prévost, E.; Baglinière, J.‐L.; Nevoux, M.
Abstract : This study provides new data on Atlantic salmon Salmo salar life‐history traits across France. Using a long‐term recreational angling database (1987–2013) covering 34 rivers in three regions (genetic units), a decline in individual length, mass and a delayed adult return to French rivers was reported. Temporal similarities in trait variations between regions may be attributed to common change in environmental conditions at sea. The relative rate of change in phenotypic traits was more pronounced in early maturing fish [1 sea‐winter (1SW) fish] than in late maturing fish (2SW fish). Such contrasted response within populations highlights the need to account for the diversity in life histories when exploring mechanisms of phenotypic change in S. salar . Such detailed life‐history data on returning S. salar have not previously been reported from France. This study on French populations also contributes to reducing the gap in knowledge by providing further empirical evidence of a global pattern in S. salar across its distribution range. Results are consistent with the hypothesis that the observed changes in life‐history traits are primarily associated with environmental changes in the North Atlantic Ocean. They also emphasize the presence of less important, but still significant contrasts between region and life history.